2012
DOI: 10.1007/s10661-012-3018-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of irrigation with wastewater on the physiological properties and heavy metal content in Lepidium sativum L. and Eruca sativa (Mill.)

Abstract: The purpose of this study was to determine the physiological properties of and heavy metal content in Lepidium sativum L. and Eruca sativa (Mill.) irrigated with municipal wastewater for 20 days. Wastewater was taken from a section where all wastewater of Adiyaman is collected. We analysed the soil for physicochemical properties, heavy metals and nutrient content and the plants for photosynthetic pigment content, dry weight and length. Irrigation wastewater increased the electrical conductivity and organic mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…The our results confirm that copper accumulation in plants depends on the concentration of metal ions in the growing medium [14,34].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The our results confirm that copper accumulation in plants depends on the concentration of metal ions in the growing medium [14,34].…”
Section: Discussionsupporting
confidence: 85%
“…Effects of metals have been studied intensively at the level of biochemical-physiological and metal accumulation in plant tissue [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several studies have emphasized the risks of heavy metal accumulation in topsoils irrigated with wastewater [15][16][17][18][19]. Furthermore, several studies have demonstrated that wastewater-irrigated plants may absorb and accumulate heavy metals at concentrations that are greater than the maximum permissible limits, which can result in serious public health problems [20][21][22]. Although Shah et al [7] studied the accumulation of heavy metals in different plants, few studies have been published regarding the accumulation of heavy metal in different plant organs.…”
Section: Introductionmentioning
confidence: 99%
“…There was no signifi cant difference between the use of treated effl uents and topdressing for reduction in the mineral fertilisers spending. Keser ( 2013 ) showed that the use of wastewater for irrigation in Turkey increased heavy metal content in both Lepidium sativum L. and Eruca sativa (Mill.) and affected their physiological and morphological properties.…”
Section: Cropsmentioning
confidence: 99%